The Dynamics of Differences in Schools of Thought in Households: A Review of Islamic Family Law and Case Studies - Sandika Saputra; Sholihin Shobroni (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
The differences in religious schools of thought are highly likely to lead to marital conflict due to differing views and opinions regarding religious practices. The aim of this study is to investigate the impact of marriages between adherents of different schools of thought and their legal and social implications. The method of this research is qualitative research, with literature review analysis. The impact of differences in schools of thought in households consists of 3 impacts, namely Social, Doctrinal, and Psychological. On the social impact, differences in schools of thought apparently nearly destroyed the marriage of the couple. On the doctrinal impact, differences in schools of thought within marriage can create significant discomfort, particularly when one partner resists adopting the practices of the other. On the psychological impact, differences in schools of thought can become a strength in building a strong and blessed family. Furthermore, this research contributes to the discourse on Islamic family law and inter-maddhab marriage. The practical implication of this research is that it can inspire family consultants regarding inter-madhhab marriage. Further research can be discussed from the legal aspect of marriages between different madhhabs.